Research on the algorithm for reducing the PAPR of OFDM system based on quantum chaotic mapping - Yingjie MA; Geng ZHAO; Zhanzhen WEI; Zhaobin LI; Lei JU (Tongxin xuebao)
Aiming at the high peak to average power ratio (PAPR) problem of OFDM system,a modified selective mapping algorithm based on quantum loigstic chaotic map was proposed.To solve the problem of fixed point and stable window,the quantum loigstic chaotic maps were used as random phase sequence vectors,which provided a large number signals with fine correlation and random characteristics,easy to produce and regenerate.Matlab simulation results show that the proposed algorithm effectively reduces the PAPR,increases the numbers of candidate signals,cuts down the amount of redundant information transmission,bring down the side band power.The proposed scheme has a broad application prospect in OFDM system.